Pola Konsumsi Orang Dewasa Minangkabau dan Hubungannya Dengan Ukuran Lingkar Pinggang: Consumption Patterns of Minangkabau Adults and Relationship with Waist Circumference Measure - Susmiati (Fakultas Keperawatan Universitas Andalas, 2012)
This study used Cross Sectional Study design comprising the population of adult’s group age 30-60 years, live in Padang. 54 samples were taken by multi stage method from Bungus, Teluk Kabung, and Kecamatan Nanggalo. Data were taken by interview about dietary intake using Food Frequency Questionnaires (FFQ) and anthropometric measurement (body weight, height, and waist circumference). Then, data were analyzed with Spearman correlation analysis. This study revealed that respondents with waist circumference above average were 29 persons (53,7%) and normal were 25 persons (46,7%). Average energy, protein, fat, carbohydrate, and fiber was higher in the respondents with abnormal waist circumference that in those with normal. There was a significance difference between average consumption of energy, protein, fat, carbohydrate, and fiber between respondents with normal and abnormal waist circumference (p<0.05). Using correlation analysis on consumption rates (energy, protein, fat, carbohydrate, and fiber) on waist circumference, it was found that all consumption rates were significantly correlated with waist circumference (p<0.05). The strongest correlation was found with energy consumption with rho 0.719.